On-line monitoring of rotor shorted turns - Jenkins, M.P (International Conference on Life Management of Power Plants, 1994)
Large generators for use with steam and gas turbines are subject to high mechanical and electrical stress which may lead to deterioration of the insulation. The rotors, in particular, may develop short circuits and there is a need for the operators to be aware of this situation. The manner in which shorted turns can occur in the rotors of generators and the difficulties associated with monitoring for such shorted turns are indicated. An online monitor which has been developed to solve this problem is described together with some operating experiences which have been learnt from the use of it.